Blockchain Technology for Manufacturing Sector - K, Lakshminarayana; Kulkarni, Praveen; Dandannavar , Padma S; S. Tigadi, Basavaraj; Gokhale, Prayag; Naik, Shreekant (EAI Endorsed Transactions on Internet of Things, 2024)
With technology advancing rapidly, organizations must continuously develop to remain competitive. They invest in technologies such as blockchain, artificial intelligence, machine learning, and cloud computing. This study focuses on the challenges of implementing blockchain technology in the manufacturing sector. Data was collected through structured interviews with production and design managers, as well as employees of organizations using new technologies. The snowball sampling method was employed, and analysis was conducted using the large group decision method. The findings will have significant implications for leveraging blockchain in manufacturing. The study focuses on exploring factors related to opportunities and challenges within the technology organisation's environment, addressing existing research gaps. The findings are constrained by the scope of the data series, presenting longitudinal facts. To tackle the prospects and complications highlighted in the study, organizations should make use of this technology to enhance their manufacturing processes.
Keywords: Blockchain technology; Industry 4.0; Decision Making Model